Preconception care practices among primary health care nurses working in public health facilities in KwaZulu-Natal - Winifred Chinyere Ukoha; Ntombifikile Gloria Mtshali (Taylor & Francis Group, 2022)
Background Preconception care (PCC) is necessary to identify and deal with all the risk factors before conception. Some aspects of PCC, like folic acid supplementation, would be relevant to people desiring a pregnancy. Alternatively, PCC could provide contraceptive support to those with no pregnancy intention. In South Africa, primary healthcare nurses provide a comprehensive package of essential services in public health facilities to about 90% of the population at no cost. Therefore, they are the key providers of promotive, preventive, and curative services, including PCC. Objective This study aimed to determine the level of PCC practice among primary healthcare nurses and identify determinants of effective practice. Methods This cross-sectional descriptive survey was conducted among 196 nurses undertaking a specialisation Primary HealthCare program in a selected higher education institution. A pretested questionnaire was used to collect data that were analysed with SPSS version 27 software. Results The overall practice of PCC was 87.8%. Older participants were significantly less likely to exhibit good PCC practice than their younger counterparts. Female participants were also less likely to have good PCC practices than their male counterparts. Married participants were significantly more likely to practice PCC than their unmarried counterparts. Participants practicing in rural areas were also less likely to have good PCC practices than their urban counterparts. Conclusion The PCC practice of most primary healthcare nurses in the study is relatively high. The study also identified the determinants of good PCC practice that can enhance its practice. There is a need to revisit the PCC training of healthcare workers, as most indicated the need for further training.